APPLICATION OF DISCIPLINARY PUNISHMENT AGAINST PRISONERS WHO ESCAPE AT CLASS II A TEMBILAHAN CORRECTIONAL INSTITUTION - Zulkarnain S; Ahlan Surya Sari; Heni Susanti (International Conference On Law And Social Sciences, 2024)
The implementation of inmate development in correctional institutions is a way out to foster and also to return prisoners to the right path. The deviant behaviors that they once did are expected not to happen again and they can turn into members of society who behave well. This research is carried out in with the main problems, namely: 1) How is the implementation of the application of sanctions against prisoners who escape in class II A Tembilahan Correctional Facility. 2) How are the efforts made by correctional institutions in preventing prisoners from escaping in Correctional Facility II A Tembilahan. This study uses a juridical approach to sociological juridical research / sociology of law, namely a research approach that studies the influence of society on the law, the extent to which the symptoms that exist in society can affect the law and vice versa and depart from the empirical science paradigm. The results of this study explain that the implementation of the application of sanctions against prisoners who escape is by giving sanctions of severe disciplinary punishment in the form of being placed in a seclusion cell for 2 (two) times 6 (six) days and not given their rights in the form of remission, family visitor leave, conditional leave, assimilation, leave before release and parole. Based on the research, the efforts made by the Prison Institute in preventing prisoners from escaping are by taking an approach, prisoners are given their rights, coaching is held and coaching is given to employees in the form of physical, mental and disciplinary coaching.